Indigenous rights in Latin America and Peru: An intercultural approach - Pérez-Romero, James Obed; Pozo Johanson, Katherin; Rivera-Gamarra, Ana Carolina; Reyes Cuba, Claudia Katherine (Revista de Ciencias Sociales, 2024)
The rights of indigenous peoples have been a highly debated topic in Latin American scenarios, being the result of a process of collective struggles to achieve social demands. It is a historical fact that contemplates a series of mechanisms that guarantee the protection of the indigenous populations of the region. By virtue of the above, this paper aims to evaluate the role of the law, as well as its degree of compliance in safeguarding the integrity of aboriginal populations in Latin America and Peru. The method used is that of documentary exploration, which contemplates the selection of bibliographic material from specialized academic sources. Among the main findings is that indigenous law has achieved relevance after the efforts made by international organizations such as the International Labor Organization and the United Nations. Likewise, in the Peruvian context, the current Political Constitution guarantees the protection of diversity, but, beyond the recognition of multiculturalism, the law must seek an intercultural approach as a mechanism to stop exclusion. It is concluded that interculturality is an effective mechanism to provide access to the right to dignity for indigenous populations.